2018
DOI: 10.1111/codi.13902
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor and its correlation with clinical symptoms and endoscopic findings in patients with chronic radiation proctitis

Abstract: A significant increase in VEGF expression was found to correlate with clinical symptoms and endoscopic rectal mucosa changes in patients with ChRP, suggesting that it may play an important role in pathological angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(139 reference statements)
0
3
0
2
Order By: Relevance
“…Ghorbanzadeh-Moghaddam et al (59) demonstrated that Vitamin D deficiency predisposes to the development of severe acute radio-induced proctitis, promoting its correction when necessary. The increased expression of vascular endothelial growth factor (VEGF) in response to radiation damage could be the basis of clinical symptoms and endoscopic rectal mucosa changes in patients with chronic proctitis: it seems responsible for abnormal sprouting angiogenesis which endoscopically manifests itself with telangiectases tending to easily bleed (60). Microvascular density was significantly increased in post-irradiated rectal mucosa biopsies and related to an increased expression of VEGF and CD31, similarly to the work of Karamanolis (61).…”
Section: Increased Understanding Of Pathogenesis and Predictive Signatures Supporting Possible Therapeutic Implicationsmentioning
confidence: 78%
“…Ghorbanzadeh-Moghaddam et al (59) demonstrated that Vitamin D deficiency predisposes to the development of severe acute radio-induced proctitis, promoting its correction when necessary. The increased expression of vascular endothelial growth factor (VEGF) in response to radiation damage could be the basis of clinical symptoms and endoscopic rectal mucosa changes in patients with chronic proctitis: it seems responsible for abnormal sprouting angiogenesis which endoscopically manifests itself with telangiectases tending to easily bleed (60). Microvascular density was significantly increased in post-irradiated rectal mucosa biopsies and related to an increased expression of VEGF and CD31, similarly to the work of Karamanolis (61).…”
Section: Increased Understanding Of Pathogenesis and Predictive Signatures Supporting Possible Therapeutic Implicationsmentioning
confidence: 78%
“…Таким образом, орошение формалином имеет ограниченное применение у пациентов с легкой степенью ХЛП. Также следует принимать во внимание высокую вероятность побочных эффектов (до 40-70 %) [3,6,32]. Кроме того, техника выполнения манипуляции, концентрация формалина и показатели эффективности лечения, о которых сообщалось в различных исследованиях, сильно различаются [26].…”
Section: -4' 2020unclassified
“…Использование конформной и интенсивно модулированной лучевой терапии, активное применение брахитерапии при раке тазовой локализации позволило значительно повысить эффективность лечения и частоту полных ответов. Однако частота поздних лучевых повреждений прямой кишки остается достаточно высокой и достигает 5-20 % [3].…”
unclassified
“…Many previous reports focus on the various methods used for treating ongoing inflammation but fail to address its pathophysiology. There is therefore the need for a better understanding of the precise mechanisms underlying radiation-induced proctitis to determine best methods of protection and treatment 7 . Sildenafil, which was developed for the treatment of erectile dysfunction, inhibits cyclic guanosine monophosphatespecific phosphodiesterase-5, an enzyme that is abundantly present in the pulmonary vasculature, and thereby promotes nitric oxide-mediated vasodilatation, which in turn decreases pulmonary vascular resistance 8,9 .…”
Section: ■ Introductionmentioning
confidence: 99%